2014
DOI: 10.1038/nrurol.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic basal and luminal subtypes of muscle-invasive bladder cancer

Abstract: Whole-genome analyses have revealed that muscle-invasive bladder cancers (MIBCs) are heterogeneous and can be grouped into basal and luminal subtypes that are highly reminiscent of those found in breast cancer. Basal MIBCs are enriched with squamous and sarcomatoid features and are associated with advanced stage and metastatic disease at presentation. Like basal breast cancers, basal bladder tumours contain a claudin-low subtype that is enriched with biomarkers characteristic of epithelial-to-mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
248
2
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(273 citation statements)
references
References 116 publications
10
248
2
13
Order By: Relevance
“…Actually, gene expression studies have identified different intrinsic subtypes of MIBC such as basal and luminal ones, similar to those found in breast cancer [69]. Basal BC seems to be intrinsically aggressive and associated with advanced stage and metastases at diagnosis and, therefore, with worse survival outcomes compared with the luminal subtype [70]. Surprisingly, HER2 overexpression is a well-known characteristic feature of luminal BC [10,71].…”
Section: Her2 and Molecular Typing Of Bcmentioning
confidence: 92%
“…Actually, gene expression studies have identified different intrinsic subtypes of MIBC such as basal and luminal ones, similar to those found in breast cancer [69]. Basal BC seems to be intrinsically aggressive and associated with advanced stage and metastases at diagnosis and, therefore, with worse survival outcomes compared with the luminal subtype [70]. Surprisingly, HER2 overexpression is a well-known characteristic feature of luminal BC [10,71].…”
Section: Her2 and Molecular Typing Of Bcmentioning
confidence: 92%
“…It is almost never associated with human papillomavirus infection, with the rare exception of some cases with a basaloid morphology [67,68]. Interestingly, recent genomic data have described a basal/squamous-like molecular subtype that has squamoid morphology and immunophenotype and is associated with poor survival and poor response to systemic therapy [69,70]. Glandular neoplasms constitute the second most common form of divergent differentiation, seen in up to 18% of invasive tumours and defined by the presence of gland formation [71][72][73].…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…Although essentially unaddressed in lung cancer, a claudin-low phenotype has been linked to EMT, stemness, and chemotherapy resistance in breast and bladder cancer (36)(37)(38). CLDN7 is known to inhibit human lung cancer invasion (15), and low expression of CLDN7 is linked to poor prognosis in NSCLC (39).…”
Section: Discussionmentioning
confidence: 99%